Development in the Regulation of Wages and Working Conditions: The Employee Perspective - Høgedahl, Laust; Jørgensen, Henning (Nordic Journal of Working Life Studies, 2017)
The Nordic countries are renowned for their high level of unionization and collective bargaining. However, globalization, Europeanization, and an increasing individualization are often pictured as factors suppressing collective regulation. In this article, we look at the developments in the regulation of wages and working conditions from a macro perspective by combing two large cross- sectional surveys into a longitudinal study with point of departure in the Danish case. We find that collective bargaining coverage continues to stand surprisingly strong, both in terms of being very widespread and in employee awareness, but Danish wage and salary earners also have an interest in extra support in the form of generalization and/or a politically regulated minimum wage